Current understanding of the mixed pain concept: a brief narrative review (2019)
Despite having been referenced in the literature for over a decade, the term “mixed pain” has never been formally defined. The strict binary classification of pain as being either purely neuropathic or nociceptive once left a good proportion of patients unclassified; even the recent adoption of “nociplastic pain” in the IASP Terminology leaves out patients who present clinically with a substantial overlap of nociceptive and neuropathic symptoms. For these patients, the term “mixed pain” is increasingly recognized and accepted by clinicians. Thus, an independent group of international multidisciplinary clinicians convened a series of informal discussions to consolidate knowledge and articulate all that is known (or, more accurately, thought to be known) and all that is not known about mixed pain. To inform the group’s discussions, a Medline search for the Medical Subject Heading “mixed pain” was performed via PubMed. The search strategy encompassed clinical trial articles and reviews from January 1990 to the present. Clinically relevant articles were selected and reviewed. This paper summarizes the group’s consensus on several key aspects of the mixed pain concept, to serve as a foundation for future attempts at generating a mechanistic and/or clinical definition of mixed pain. A definition would have important implications for the development of recommendations or guidelines for diagnosis and treatment of mixed pain. © 2019, © 2019 Informa UK Limited, trading as Taylor and Francis Group.